THE GERMINATION OF SALAK (Salacca zalacca) SEEDS WITH CHEMICAL SCARIFICATION TREATMENT : GERMINATION OF SALAK (Salacca zalacca) SEEDS WITH CHEMICAL SCARIFICATION TREATMENT - Siregar, Elda Sari; Mahmud, Amir; Lubis, Rafiqah Amanda; Permadi, Muhammad Agung; Daulay, Ramadhan Syaputra (Jurnal Online Pertanian Tropik, 2021)
This study aims to determine the effect of KNO3, H2SO4, and GA3 in breaking dormancy and germination of salak (Salacca zalacca) plants. In this study using a non-factorial randomized block design with one factor, namely P0 (control), P1 (KNO3 60%), P2 (KNO3 70%), P3 (KNO3 80%), P4 (H2SO4 60%), P5 (H2SO4 70%), P6 (H2SO4 80%), P7 (GA3 25 ppm), P8 (GA3 50 ppm), P9 (GA3 75 ppm), P10 (KNO3 60% and GA3 25 ppm), P11 (KNO3 70% and GA3 50 ppm), P12 (KNO3 80% and GA3 75 ppm), P13 (H2SO4 60% and GA3 25 ppm), P14 (H2SO4 70% and GA3 50 ppm), P15 (KNO3 60% and GA3 75). Parameters observed were germination, maximum growth potential, plant height, number of leaves, leaf length, and leaf width. Based on the results of the DMRT test at 5% level, it showed that each treatment had an effect on the chemical scarification treatment showing a significant effect on germination, maximum growth potential, plant height, number of leaves, leaf length, and leaf width. However, it did not have a significant effect on the number of leaves at 12 WAP, leaf width at 11 and 12 WAP. Keywords: Plant Height, Leaves, Leaf Width